Can education compensate the effect of population ageing on macroeconomic performance?. (10th August 2018) - Kotschy, Rainer; Sunde, Uwe
Abstract: This paper investigates the consequences of population ageing and of changes in the education composition of the population for macroeconomic performance. Estimation results from a theoretically founded empirical framework show that ageing as well as the education composition of the population influence economic performance. The estimates and simulations based on population projections and different counterfactual scenarios show that population ageing will have a substantial negative consequence for macroeconomic performance in many countries in the years to come. The results also suggest that education expansions tend to offset the negative effects, but that the extent to which they compensate the ageing effects differs vastly across countries. The simulations illustrate the heterogeneity in the effects of population ageing on economic performance across countries, depending on their current age and education composition. The estimates provide a method to quantify the increase in education that is required to offset the negative consequences of population ageing. Counterfactual changes in labour force participation and productivity required to neutralise ageing are found to be substantial.